Transcranial brain-wide functional ultrasound and ultrasound localization microscopy in mice using multi-array probes - Mathis Vert; Ge Zhang; Adrien Bertolo; Nathalie Ialy-Radio; Sophie Pezet; Bruno Osmanski; Thomas Deffieux; Mohamed Nouhoum; Mickael Tanter (Scientific Reports)
Abstract Functional ultrasound imaging (fUS) and ultrasound localization microscopy (ULM) are advanced ultrasound imaging modalities for assessing both functional and anatomical characteristics of the brain. However, the application of these techniques at a whole-brain scale has been limited by technological challenges. While conventional linear acoustic probes provide a narrow 2D field of view and matrix probes lack sufficient sensitivity for 3D transcranial fUS, multi-array probes have been developed to combine high sensitivity to blood flow with fast 3D acquisitions. In this study, we present a novel approach for the combined implementation of transcranial whole-brain fUS and ULM in mice using a motorized multi-array probe. This technique provides high-resolution, non-invasive imaging of neurovascular dynamics across the entire brain. Our findings reveal a significant correlation between absolute cerebral blood volume (ΔCBV) increases and microbubble speed, indicating vessel-level dependency of the evoked response. However, the lack of correlation with relative CBV (rCBV) suggests that fUS cannot distinguish functional responses alterations across different arterial vascular compartments. This methodology holds promise for advancing our understanding of neurovascular coupling and could be applied in brain disease diagnostics and therapeutic monitoring.